Vila-Viçosa, C & Almeida, R. (2020) Lectotypification of names of Quercus spp. (Fagaceae) described by Lamarck from the Iberian Peninsula. Phytotaxa 455 (3): 205–213 - Vila-Viçosa, Carlos; Almeida, Rubim (Phytotaxa, 2020)
N/A